(untitled) (Religious dialogue and cooperation, 2025)
In today’s era of rapid globalization and change, humanity enjoys unprecedented convenience and connectivity, yet faces value conflicts, social injustice, and cultural homogenization that threaten global peace and coexistence. Confronted with this global moral crisis, Conscience Culture is emerging as a vital pathway for building consensus and restoring a shared ethical and value-based foundation. As a universal value that transcends religions, cultures, and ideologies, conscience serves not only as an inner moral compass for individuals but also as a crucial driver of practical action, international cooperation, and mutual trust. This paper draws on the Ti-Yong (Essence- Function) concept of Tai Ji Yin-Yang Philosophy, positioning conscience as the core essence (體, ti) of culture and morality, while its external expression (用, yong) is realized through moral intuition (良知, liangzhi) and moral capability (良能, liangneng). Together, these guide individual action and institutional design, achieving an organic integration of inner awareness and the practice of justice. Using Tai Ji Men’s global conscience and peace initiatives as examples, this paper demonstrates how the cultural resilience of Conscience Culture—flexible yet firmly rooted—can help resolve the tensions and challenges posed by contemporary globalization. It further shows how Conscience Culture can guide humanity toward peace, fairness, and the moral renewal of humankind, opening new horizons for “global civilization.”